The methodological matter in print journalism (RuMoRes, 2008)
Some brazilian researchers have been tracing, more expressively in the last years, the profile of the journalism research in Brazil. The approaches have a broad aim, with subject survey, technological support and research lines. I would like to start from these conjunct of works proposed in macro-analysis to question, specifically, methodological options in journalism studies that take as basis newspaper articles.